Germ cells - Surani, Azim (Henry Stewart Talks, 2007)
The germ cell cycle and the key epigenetic programming events in the germ cell lineage, the oocyte and its properties, epigenetic mechanism of germ cell specification in mice, repression of the somatic programme, a key event during specification of germ cells, epigenetic programming following specification of germ cells, the relationship between germ cells and pluripotent stem cells
Archived at 2018/05/31